2012
DOI: 10.1093/ije/dys162
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association studies in pre-eclampsia: systematic meta-analyses and field synopsis

Abstract: To date, candidate gene studies in pre-eclampsia have not robustly documented any associations with strong epidemiological credibility. Large-scale replication of the most promising associations, exhibited by two genetic variants, and incorporation of agnostic high-throughput data may improve our genetic knowledge base for this complex phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 47 publications
2
43
1
2
Order By: Relevance
“…A meta-analysis8 that included 27 studies showed that AGT rs699 was significantly associated with PE (OR = 1.26, 99% CI: 1.00, 1.59), but the included studies had high heterogeneity (I 2  = 70%). Another meta-analysis15 investigated the association between AGT rs699 and PIH in Chinese population and found significant associations in dominant genetic model, recessive genetic model, and allelic model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis8 that included 27 studies showed that AGT rs699 was significantly associated with PE (OR = 1.26, 99% CI: 1.00, 1.59), but the included studies had high heterogeneity (I 2  = 70%). Another meta-analysis15 investigated the association between AGT rs699 and PIH in Chinese population and found significant associations in dominant genetic model, recessive genetic model, and allelic model.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, no association between the abovementioned SNPs and PIH has been reported in this population. Although AGT rs699 and AGTR1 rs5186 have been extensively studied for their association with PIH and a meta-analysis8 showed that they are significantly associated with PE, the high heterogeneity among studies necessitates additional confirmation.…”
mentioning
confidence: 99%
“…However, attempts to replicate these findings yielded inconsistent results. In a meta-analysis including 192 genetic association studies, 25 replicated genetic variants were identified [60]. Another meta-analysis identified 542 genetic association studies and included 22 independent meta-analyses [61].…”
Section: Discussionmentioning
confidence: 99%
“…Il souligne un lien entre la PE et l'exposition au sperme, donc aux antigènes paternels [19] ; le deuxième est la mise en évidence de l'importance de la la génétique maternelle, 20 % à la génétique foetale, 13 % à un effet « couple », moins de 1 % à un effet environnemental partagé par les apparentées, et 32 % à des facteurs inconnus [11]. Des variants génétiques de gènes cibles impactent également le risque de déve-lopper une PE (pour une revue voir [12]), comme les gènes codant les facteurs 2 et 5 de la coagulation (F5, F2), l'angiotensinogène (AGT) et son récepteur (AGTR1), ou l'enzyme de conversion de l'angiotensinogène (ACE). Des études familiales ont également permis de relier des régions génomiques au risque de PE, avec l'identification de gènes comme STOX1 (storkhead box 1) 1 , ou TNFSF13B (TNF superfamily member 13b) 2 .…”
Section: Bases Immunologiques De La Prééclampsieunclassified